Studi Kelayakan Analisis Dampak Lingkungan pada PT Bank Maybank Indonesia Tbk - Abdillah, Mochammad Nizar (Maliki Interdisciplinary Journal, 2025)
In general, industrial activities are able to ensure the continuity of the development process of a region, and industry is one of the sectors that plays an important role in regional development and development. According to PP no. 27 of 1999, AMDAL is defined as a study of large and important impacts for decision making regarding planned businesses or activities on the environment which is necessary for the decision making process regarding the implementation of businesses or activities. The average feasibility evaluation score recorded at 5 indicates that from the AMDAL aspect, Bank Maybank has very good performance in terms of business feasibility. Industrial activities are an important component in regional development and construction. Submission of environmental permits is impossible without AMDAL. In addition, the requirement for submitting an application for a business permit (sectoral) is an environmental permit.